PENGEMBANGAN PERMAINAN EDUKATIF DEEP LEARNING KOMPONEN KEKUATAN KEBUGARAN JASMANI BERBASIS FLIPBOOK PADA SISWA KELAS VII - Thoyib Prayogo; Siti Nurrochmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of this digital flipbook media focuses on the integration of various forms of educational games that utilize deep learning in the context of physical fitness, particularly in the aspect of muscle strength components, aimed at seventh-grade students at SMP Negeri 2 Malang. In its implementation, this research follows the Research and Development (R&D) methodology path by adopting the ADDE (Analysis, Design, Development, and Evaluation) development model which is an adaptation of the widely known ADDIE model. The validation process in this study involved two experts, each acting as a validator in the field of learning materials and a validator in the field of media development. The data collection instrument used a 1–4 Likert scale validation sheet analyzed using descriptive percentage techniques. The resulting product is a digital flipbook media containing a structured learning storyboard combined with a video guide for a deep learning-based educational game. The validation results show that the product obtained a very valid category from both material experts (95.5%) and media experts (88.2%). The needs analysis revealed a gap between the high interest of students in PJOK and the low utilization of digital media in learning. This product not only develops physical muscle strength, but also encourages deep and reflective conceptual understanding through a deep learning approach, thus realizing holistic, interactive, and student-centered PJOK learning.